1997
DOI: 10.4158/3.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Coronary Angiographic Contrast Agents on Thyroid Function

Abstract: Objective: To determine the effect of two iodine-containing contrast agents used for coronary angiography on subsequent thyroid hormone concentrations. Methods: We prospectively studied thyroid function in 56 patients, with no previous history of thyroid disease and normal findings on thyroid examinations, who underwent nonemergent cardiac catheterization. Thyroid hormone concentrations were assessed at baseline and at day 1 and day 7 after administration of a radiographic iodinated contrast agent (Renografin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In contrast, an Italian study of over 1700 patients reported a low incidence of hyperthyroidism of 1.9% after coronary angiography (43). Similarly, hyperthyroidism was not seen in a US study of 56 patients who underwent coronary angiography (44). The low rate of contrast-induced hyperthyroidism in the Italian study, conducted in an iodine-deficient region, was likely due to the use of antithyroid medications and/or radioactive iodine ablation before contrast exposure.…”
Section: Contrast-induced Hyperthyroidismmentioning
confidence: 85%
“…In contrast, an Italian study of over 1700 patients reported a low incidence of hyperthyroidism of 1.9% after coronary angiography (43). Similarly, hyperthyroidism was not seen in a US study of 56 patients who underwent coronary angiography (44). The low rate of contrast-induced hyperthyroidism in the Italian study, conducted in an iodine-deficient region, was likely due to the use of antithyroid medications and/or radioactive iodine ablation before contrast exposure.…”
Section: Contrast-induced Hyperthyroidismmentioning
confidence: 85%
“…Hence, the usual knowledge on that particular problem is rather insufficient and studies considering this clinical entity are relatively scarce. Two studies in Germany and the USA showed that only a small proportion of patients after coronary angiography or computed tomography scan develop subclinical hypothyroidism 11,12 . It is usually established approximately 1 week after the examination.…”
Section: Discussionmentioning
confidence: 99%
“…The most rapid (hours to days) effect of pharmacologic doses of iodine is to inhibit organification of iodide, thereby diminishing hormone biosynthesis (Wolff-Chaikoff effect) and decreasing thyroglobulin proteolysis, thereby decreasing thyroid hormone secretion [3, 5]. The resulting small decrease in serum T4 and T3 levels causes a compensatory, transient increase in TSH concentrations [44, 45]. After the acute phase, normal thyroid hormone synthesis resumes, even with continued excess iodide exposure, a phenomenon described as the escape from the acute Wolff-Chaikoff effect.…”
Section: Recommendationsmentioning
confidence: 99%